ANALISIS PELAKSANAAN PENILAIAN OLEH GURU MATA PELAJARAN BIOLOGI SMA KELAS X DI KABUPATEN INDRAGIRI HULU DALAM MENCAPAI STANDAR NASIONAL PENDIDIKAN - Sepada Asmarika Kadir; Evi Suryawati; R. Hussien Arief ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to analyze the technical feasibility level assessments byteachers in implementing the evaluation of learning biology in the implementation ofthe curriculum in 2013, and to analyze the quality of items replay end of the semesterthe class X SMA Indragiri Hulu artificial 2014/2015 school year teachers based ondifficulty level , distinguishing features and grains detractors. The research sample foranalysis of the implementation of the assessment is taken as many as 10 schools thathave implemented the curriculum in 2013 and incorporated in the MGMP. The researchsample for analysis item which is about the end of the semester artificial replications 3different groups of MGMPs biology. Data collected the primary data in the form ofinterview guidelines and documentation as well as secondary data in the form ofquestions and answer sheets replicates end of the semester. The data analysis techniqueused is descriptive analysis with percentages. Based on the results obtained penelititanthat the level of feasibility assessment by subject teachers SMAN biology class X inIndragiri Hulu has not yet reached the National Education Standards. Assessment doneby teachers is a written assessment by the average percentage of 100% with a very goodcategory. Test questions difficulty level items Biology class X semester first semesterSMAN in Indragiri Hulu TP 2014/2015 obtained an average 27.5% a matter of simplecategories: average 47.5%: difficult 25%. For distinguishing items replay semesteraverage gained about the ugly category of 29.2%: just 30%: 20% Good: excellent8.3%: 12.5% negative. Item humbug (distractors) which serves good (D≥5%) gained anaverage of 13.3% while distractors were not functioning properly (D <5%) 86.7%.Key Words: Analysis Assessment , Lessons Biology , National Education Standards